A case of paraparesis with thoracic ossification of the posterior longitudinal ligament and the ligamentum flavum induced by falling down on the abdomen. Issue 1 (10th November 2013) - Nagayama, Masataka; Yanagawa, Youichi; Okuda, Takatoshi; Yonezawa, Ikuho; Iba, Toshiaki; Kaneko, Kazuo
<x xml:space="preserve">Abstract</x> Aim To describe an educational case. Methods Case report. Results A 71‐year‐old female was transported to our emergency department with complaints of lower abdominal pain and gate disturbance after falling down on her abdomen. She had lower abdominal painful paresthesia in the dermatome from the twelfth thoracic to the first lumbar level without signs of peritoneal stimulation. Paraparesis and dysesthesia of the lower extremities was predominant on the left side. Abdominal computed tomography revealed severe thoracic ossification of the posterior longitudinal ligament and the ligamentum flavum at the thoracic level 10/11. Laminectomy and spinal fusion with rods resulted in recovery of the patient's symptoms. Conclusion Physician should pay attention to thoracic spinal cord injury induced by hyperextensive stress on the spine, even in cases of minor trauma, among patients with preexisting bony pathologies at the thoracolumbar level.